Effects of grain size and precipitation on liquation cracking of AZ61 magnesium alloy laser welding joints. (1st August 2013) - Chen, X L; Yan, H G; Chen, J H; Su, B; Yu, Z H
<x xml:space="preserve">Abstract</x> Four kinds of wrought AZ61 alloy sheets with different microstructural features were successfully welded by CO2 laser beam butt welding. Welding joints without visible pores were obtained under optimum process parameters. Effects of grain size and precipitation on liquation cracking behaviours of the laser welding joints were investigated. As far as the as rolled alloy sheets were concerned, liquation in the partially melted zone (PMZ) was visible along grain boundaries, and the extent of liquation was more serious in the alloy sheets with larger grains. As far as the as aged alloy sheets were concerned, plenty of precipitates (β-Mg17Al12) were involved and liquation in the PMZ was found both at grain boundaries and within grains. Moreover, the extent of liquation was more serious in the alloy sheets with more precipitates. It is promising to reduce liquation cracks in the PMZ of magnesium alloys by grain refinement, reducing the size and the quantity of the low melting point phase, and modifying its distribution.